Transcranial direct current stimulation for focal status epilepticus or lateralized periodic discharges in four patients in a critical care setting. Issue 4 (7th February 2023) - Fisher, Robert S.; McGinn, Ryan J.; Von Stein, Erica L.; Wu, Teresa Q.; Qing, Kurt Y.; Fogarty, Adam; Razavi, Babak; Venkatasubramanian, Chitra
Abstract: Objective: Transcranial direct current stimulation (tDCS) has been advocated for various neurological conditions, including epilepsy. A 1–4‐mA cathodal current applied to the scalp over a seizure focus can reduce spikes and seizures. This series of four patients with focal status epilepticus is among the first case series to demonstrate benefit of tDCS in the critical care setting. Methods: Patients in the intensive care unit were referred for tDCS treatment when focal status epilepticus or clinically relevant lateralized periodic discharges did not resolve with conventional antiseizure medications and anesthetics. Battery‐powered direct cathodal current at 2 mA was delivered by an ActivaDose (Caputron) tDCS device via a saline‐soaked sponge on the scalp over the seizure focus. Anode was on the contralateral forehead or shoulder. Treatment was for 30 min, repeated twice in a day, then again 1–4 times more over the next few days. Results: Three females and one male, aged 34–68 years, were treated. Etiologies of status epilepticus were posterior reversible encephalopathy syndrome in association with immunosuppressants for a liver transplant, perinatal hypoxic–ischemic injury, a prior cardioembolic parietal stroke, and central nervous system lupus. tDCS led to significant reduction of interictal spikes (.78 to .38/s, p  < .0001) in three cases and electrographic seizures (3.83/h to 0/h, p  < .001) in two cases. Medication reductions were enabled in all cases subsequent to tDCS. The only side effect of tDCS was transient erythema under the sponge in one case. Two patients died of causes unrelated to tDCS, one was discharged to a nursing home, and one became fully responsive as seizures were controlled with tDCS. Significance: Spikes and electrographic seizure frequency significantly improved within 1 day of tDCS. Results are potentially confounded by multiple ongoing changes in medications and treatments. These results might encourage further investigation of tDCS in the critical care setting, but verification by controlled studies will be required.